2008
DOI: 10.1097/sla.0b013e318161312a
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity and Recurrence After Completion Lymph Node Dissection Following Sentinel Lymph Node Biopsy in Cutaneous Malignant Melanoma

Abstract: CLND is fraught with considerable morbidity. Local control of the dissected nodal basins was achieved with a modified radical approach in ADs (levels I + II only) and, to a lesser extent, GDs, but not in NDs. Clinical trials are necessary to establish guidelines on the extent of lymphatic dissection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
57
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(69 citation statements)
references
References 54 publications
9
57
0
3
Order By: Relevance
“…As a consequence, the majority of SLN-positive patients undergo unnecessary surgery associated with considerable morbidity (Guggenheim et al, 2008). Therefore, several authors have tried to identify patient, tumour and SLN characteristics predicting further non-SLN positivity to safely avoid CLND (Carlson et al, 2003;Van Akkooi et al, 2006;Scolyer et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, the majority of SLN-positive patients undergo unnecessary surgery associated with considerable morbidity (Guggenheim et al, 2008). Therefore, several authors have tried to identify patient, tumour and SLN characteristics predicting further non-SLN positivity to safely avoid CLND (Carlson et al, 2003;Van Akkooi et al, 2006;Scolyer et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…10,15 Groin dissections are, in general, associated with a greater prevalence of complications than axillary dissections, as demonstrated here and in other studies. 10,11 Patients with a high body mass index (>30 kg/m 2 ) undergoing inguinal dissection are at a greater risk of developing complications. 5,9 If undertaking groin dissections, some surgeons preserve the saphenous vein and may also transpose the sartorius muscle to provide more robust and reliable cover of inguinal vessels.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8] Groin dissections are typically associated with a higher prevalence of complications than axillary dissections. 2,[9][10][11][12] In 1992, Baas et al undertook a retrospective review of 151 consecutive groin dissections. They reported a prevalence of 17% for seroma, 9% for wound infection, 3% for wound necrosis, and 20% for wound oedema.…”
mentioning
confidence: 99%
“…Our morbidity rate is comparable with other studies on surgery for melanoma with reported rates of 19.9% to 51%. [9][10][11][12][13] However, these reports do not provide further patients' details except the primary tumour stage and, in some cases, the height, body weight and BMI. Other possible risk factors such as concomitant diseases are not mentioned.…”
Section: -32mentioning
confidence: 99%
“…There are several reports on factors influencing the morbidity rates such as the site of lymph node dissection (groin or axillary) and the body mass index (BMI) of the patients as well as the number of tumour-affected lymph nodes. [9][10][11][12][13] However, the reported morbidity rates are mostly based on multiple retrospective single institutional trials and vary widely. 14 Crude rates of morbidity and mortality after radical lymph node dissection do not allow an objective interpretation because the case mix and fitness of patients are not appropriately considered.…”
mentioning
confidence: 99%